E-Commerce e Pandemia: Comportamento de compra online antes e durante a Pandemia Covid-19 - Pires, Sofia Isabel Valério (2021)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Marketing Intelligence